Una sfida possibile: la teoria della nascita in altri ambiti linguistici - «Bisogna fare come ho fatto con l’italiano». Commento alla traduzione francese di Istinto di morte e conoscenza - Penn, Catherine (Il sogno della farfalla, 2023)
This article presents an analysis of the French translation of Death instinct and knowledge which was published in 2022, fifty years after the first Italian edition. By using the tools of translations studies and French language history, the author highlights some interesting aspects of this translation and tries to explain how the French-speaking reader may receive it. After underlining that the translation appears clearly source-oriented but designed to be accessible to him, the article shows that although Italian and French are objectively very close idioms, Fagioli’s language brings out some challenging lexical gaps between the two of them. Then the author examines several translation choices aimed at recreating the innovative and disruptive aspect of the language of the original text, from the calque fantaisie de disparition to the esprit embargo, and points out the semantic thus cultural and historical implications of these options, concluding that the translators have followed the political intention of the original.